Catawba materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Milling, Chapman J. (Chapman James), 1901-1981; Rights, Douglas L. (Douglas LeTell), 1891-1956; Speck, Florence I.; Weitluner, R. J.; Swanton, John Reed, 1873-1958; Fewkes, Jesse Walter, 1850-1930; Cadwalader, John; Haas, Mary R. (Mary Rosamond), 1910-1996; Newsome, Albert Ray, 1894-1951; Wheeler-Voegelin, Erminie, 1903-1988; Voegelin, C. F. (Charles Frederick), 1906-1986; et al. (1914)
Materials relating to Speck's study of Catawba history, language, and culture. This includes Speck's correspondence with indigenous consultants such as Red Thunder Cloud, Chief Sam Blue, and Leola Blue (Catawba) and Will West Long and Climbing Bear (Cherokee); correspondence with other anthropologists and linguists, such as John Reed Swanton, William N. Fenton, Erminie Wheeler-Voegelin, C.F. Voegelin, Morris Swadesh, A. I. Hallowell, Mary Haas, and others; genealogies of twentieth-century Catawba consultants; a Catawba bibliography; notes on topics including Catawba division of time, travel and expedition, food resources, racial status in the South, and notes, possibly for a lecture, titled "The Catawba-A Small Nation Deflated"; a University of Pennsylvania student's essay on Catawba tribal correspondence with J. Walter Fewkes about Speck's Catawba field trips; field notebooks devoted to ethnologic notes, vocabulary, texts, songs, and other linguistic and cultural data; and collections of notes devoted to Catawba language and texts, general ethnological notes, and miscellaneous notes. Some of the notes and notebooks and much of the correspondence mentions other indigenous groups as well.